ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN DI INDONESIA (Studi Kasus Pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2011-2014) - FAISAL NUGRAHA, MOCHAMAD (Jurnal Ilmu Manajemen (JIM), 2016)
The purpose of this research was to understand the influence of profitability, debt to equity ratio, firm size, growth, and cach ratio on divident payout ratio. In this research, researcher used ROA to measure profitability variable. The object of this study were firm of consumer goods industry sector listed at Indonesia Stock Exchange (IDX) period 2011-2014. This research use kuantitative approach with secondary data. The methods of data analysis in this research were multiple regression models. The result of this study indicated that, just a profitability variable which has a positive significant relationship on divident payout ratio. While the fourth other variables, such as debt to equity ratio, firm size, growth, and cash ratio have no significant relationship on divident payout ratio in firm of consumer goods industry sector. Keywords: profitability, debt to equity ratio, cash ratio, dividend payout ratio.